Studies on Socio-Demographic Pattern of Dermatomycoses Patients Attending in Rajshahi Medical College Out Patient Department (TAJ: Journal of Teachers Association, 2010)
A total of 2,194 fungal diseases patients (dermatophytoses and candidiasis) were interviewed about their socio-demographic characteristics attending the Skin and V.D. department of Rajshahi Medical College Hospital. It was found that high prevalence of diseases was in age group 21-30 years (46.63%) and females were the more suffered group (60.12%) than the males (39.88%). Among the different occupations, housewives ranked first (41.34%). Tinea corporis were highest in prevalence (44.67%) as compared to other clinical varieties of diseases. Majority of the patients were heavy sweating group (75.89%) and sweating shows a definite association with fungal diseases (P